Tingkat Kepercayaan Dan Kepuasan Pelanggan Terhadap Loyalitas Penggunaan Website hd.kfcku.com dengan Menggunakan Model E-Customer Loyalty EID - Retta Dimas Pratiwi; Yusi Tyroni Mursityo; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Website hd.kfcku.com increasingly relied upon by KFC company as an additional service provided to improve the customer experience in ordering online via the website. However at this time hd.kfcku.com website has decreased the number of subscribers to order through the website and many complaints obtained related to website services that are less than the maximum as the display of a website that is slow to respond, the address can not be detected by the website, product or goods not until the time or even the order does not arrive to the customer, the message is not immediately confirmed, and the desired information can not be accessed properly. Of the complaints received indicate that hd.kfcku.com website service is not enough to satisfy the customers. The purpose of this research is to know whether the satisfaction and trust will directly affect customer loyalty to use the website hd.kfcku.com. On this basis, the researcher tested the influence of satisfaction and trust on customer loyalty of hd.kfcku.com website by adopting E-customer loyalty EID research model through path analysis technique. Researchers use hd.kfcku.com website customers in Malang area as sample of respondents from this research. The results show that simultaneously customer loyalty is influenced by all variables of user interface quality, information quality, perceived security, perceived privacy, e-customer satisfaction and e-customer trust. While individual loyalty customers hd.kfcku.com website influenced high enough by the variable e-customer satisfaction.